Coupling the symmetrical pair of temporary pulses propagating in the focusing Kerr media. - Lasota, Szymon Jacek; Jasiński, Jerzy (Photonics Letters of Poland, 2009)
This work presents the analytical description of coupling two pulses propagating in phase one after the other. To do so the canonical method was applied. All pulses parameters are assumed to depend on the distance between them. Corresponding Euler-Lagrange equations are derived and solved. Explicit formulas describing oscillations of pulse parameters are obtained. Full Text: PDF References: G. P. Agraval, Nonlinear Fiber Optics, (San Diego, Academic Press, 2001) G.P. Agrawal, Lightwave technology:telecommunications systems, pp. 137-142, Wiley Interscience, Hoboken, 2005 D. Anderson,"Variational approach to nonlinear pulse propagation in optical fibers", Phys. Rev. A, 27, 3135, (1983)[CrossRef] H. Goldstein, C. Poole, J. Safko, Classical Mechanics, (Addison Wesley, San Francisco, 2000)